Suitability of Phytosterols Alongside Fatty Acids as Chemotaxonomic Biomarkers for Phytoplankton - Taipale, Sami J.; Hiltunen, Minna; Vuorio, Kristiina; Peltomaa, Elina (Frontiers in Plant Science, 2016)
e composition and abundance of phytoplankton is important factor defining ecological status of marine and freshwater ecosystems. Chemotaxonomic markers (e.g., pigments and fatty acids) are needed for monitoring changes in phytoplankton community and to know nutritional quality of seston for herbivorous zooplankton. Here we investigated the suitability of sterols along with fatty acids as chemotaxonomic markers by analyzing sterol and fatty acid composition of 10 different phytoplankton classes including altogether 37 strains isolated from freshwater lakes and by using multivariate statistics. We were able to detect totally 47 fatty acids and 29 sterols in our phytoplankton samples, which both differed statistically significantly between phytoplankton classes. Due to the high variation of fatty acid composition among cyanobacteria, taxonomical differentiation increased, when cyanobacteria were excluded from statistical analysis. Sterol composition was more heterogeneous within class than fatty acids and did not improve separation of phytoplankton classes when used alongside with fatty acids. However, we conclude that sterols can provide additional information on the abundance of specific genera within a class which can be generated by using fatty acids. For example, whereas high 16 ω-3 PUFAs (polyunsaturated fatty acid) indicates the presence of Chlorophyceae, simultaneous high amount of ergosterol could specify the presence of Chlamydomonas spp. (Chlorophyceae). Additionally, we found specific 4α-methyl sterols for distinct Dinophyceae genus, suggesting that 4α-methyl sterols can potentially separate freshwater dinoflagellates from each other.